Práctica y clínica con personas mayores: Herramientas de abordaje - Ferreyra, Florencia Aldana; Pereyra, María de la Paz; Arias, Claudia Josefina; Richard´s, Maria Marta (Ejes de Economía y Sociedad, 2025)
Reseña de libros